Myocarditis Complicated by Complete Atrioventricular Block: Nine Years' Experience in a Medical Center - Shao-Ju Chien; Chi-Di Liang; I-Chun Lin; Ying-Jui Lin; Chien-Fu Huang (Elsevier, 2008)
Myocarditis complicated with complete atrioventricular block (CAVB) is rare in children. The purpose of this study was to report the outcome of myocarditis with CAVB in our institution. Methods: Between June 1998 and June 2007, nine pediatric patients (aged from 1.5 to 16 years) were admitted, presenting with acute myocarditis with CAVB. We analyzed their clinical presentations, biochemistry and serology studies, chest X-rays, electrocardiograms, echocardiography, complications and outcomes. Results: Hypotension and Stokes-Adams seizures occurred in five and four of our patients, respectively. Cardiomegaly of chest X-ray was common in eight (89%) of our patients. Echocardiography revealed impaired left ventricular performance in three patients. Six patients suffered ventricular tachycardia (VT). Three cases of VT occurred before pacemaker implantation and the others occurred afterwards. Eight patients survived. Six of them regained sinus rhythm within 12 days (range 1−12 days), and two had a right bundle branch block at follow-up. Two patients had persistent CAVB, and one received permanent pacemaker implantation; the other received supportive care. One patient died due to persistent low cardiac output and a new onset of VT on the 4th admission day. During a follow-up period of 56 ± 27 months, all eight surviving patients remained asymptomatic. Conclusion: The outcome of CAVB complicated with myocarditis is variable. Most of our patients resumed normal heart function. The incidence of persistent CAVB was 22%. VT is a common and serious complication, but it can be effectively treated medically. Persistent low cardiac output after pacemaker implantation and late onset VT should be considered as risk factors of mortality.